Improving the System of Education of Youth in the Spirit of Military and Patriotism - Xujaev Botir Tavakkalovich; Rakhmonov Shavkat Zoxirovich (Genius Publishing Group, 2022)
This article describes the measures, methods and techniques to improve the system of educating young people in the spirit of military patriotism.
Keywords: Position; region; military-patriotic; Homeland